HUBUNGAN PAPARAN SINAR ULTRAVIOLET (UV) TERHADAP KEJADIAN MELASMA PADA WANITA PETUGAS PENYAPU JALAN - Azizah Dwi Kencana; Melya Susanti; Rialta Hamda (Yayasan Nusantara Hasana Berdikari, 2025)
Melasma is a hyperpigmentation disorder that commonly affects women and is influenced by various factors, including ultraviolet (UV) radiation exposure. Female street sweepers are a high-risk occupational group due to prolonged UV exposure during daily work activities, which may increase the incidence of melasma. To determine the relationship between ultraviolet (UV) exposure and the incidence of melasma in female street sweepers at the West Pasaman Regency Environmental Service in 2025, and to identify the characteristics of respondents based on age group, duration of working hours exposed to UV rays, length of work, level of UV exposure, and incidence of melasma. This study employed an observational analytic design with a cross-sectional approach. A total of 35 female street sweepers were included using total sampling technique. Melasma occurrence was assessed through clinical examination, while UV exposure levels were measured using a validated ultraviolet exposure questionnaire. Data were analyzed using univariate and bivariate statistical analyses (Chi-square). Melasma was found in 29 respondents (82.9%), while 6 respondents (17.1%) did not experience melasma. Most respondents had moderate UV exposure levels (57.1%), followed by high exposure levels (42.9%). Bivariate analysis demonstrated a statistically significant association between ultraviolet exposure and melasma occurrence (p-value = 0.02). Female street sweepers at the West Pasaman Regency Environmental Agency had predominantly moderate levels of ultraviolet (UV) exposure, with a high incidence of melasma. There was a significant relationship between ultraviolet (UV) exposure and melasma incidence among female street sweepers at the West Pasaman Regency Environmental Agency in 2025.